ANALISA PREDIKSI EFEK KERUSAKAN GEMPA DARI MAGNITUDO (SKALA RICHTER) DENGAN METODE ALGORITMA ID3 MENGGUNAKAN APLIKASI DATA MINING ORANGE - Lukman Irawan; Liyando Hermawan Hasibuan; Fauzi Fauzi (Universitas Palangka Raya, 2020)
Earthquakes are relatively common natural disasters in Indonesia, mainly due to the interaction of tectonic plates. In this study the seismic energy recorded on the seismograph was measured on the Richter Scale (SR). The dataset collected during Semester 1 of 2019 from the Meteorology and Geophysics, Climatology Agency (BMKG) noted that there were many seismic energy vibrations occurring from small to large around Indonesia. Furthermore, for the attributes of the dataset that have been collected include Date / Time, Longitude, Latitude, Depth (Km), Magnitude (SR), Range of depth (Km) and the effect of earthquake damage selected as the class of the dataset collected, in this study the authors used the method classification with ID3 algorithm to produce effective prediction data for the benefit of earthquake early warning in the Indonesian archipelago.